A Comparative Study on the Child Rearing Practices of Tribal Families and Drop out of Primary Education with Urban School - Saikia, Archana; Gopal Singha, Krishna (International Research in Education, 2023)
Indian constitution in the articles 45 has made provision for free and compulsory Education for all children us to the age of 14 years Article no 45. The data for this paper are accumulated from different sources such all Assam school survey, 2002 survey conducted by NCERT and state report cards prepared by S.D.C office of Mariani. Circle from Mariani S.D.C office. In this paper Researcher highly observed the course of drop out in primary school in the Mariani circle and comparative study of tribal and non tribal school. Comparison study of tribal and urban tribal school of Mariani finding there are so many problems of drop out. Academic difficulty, socio Economic needs poor health etc. But success of universalisation of primary education all students much be getting primary education.